Interrelation between report book and teacher performance - Witzir Sumadisastro Subran; Dinn Wahyudin; Lia Susanti; Dudun Najmudin (Inovasi Kurikulum, 2024)
Teacher report cards are a means of communication and evaluation between the principal and teachers that can improve teacher performance and impact student learning achievement. SDIT Nurul 'Ilmi Jambi has implemented teacher report cards for over ten years, which are given at the beginning of each month along with the receipt of monthly teacher rights. This study aims to determine the relationship or influence of report cards on the performance of SDIT Nurul 'Ilmi Jambi teachers. This study uses a mixed method, where data collection is carried out by distributing questionnaires. Then, to analyze the data, SPSS tools are used with validity tests, reliability tests, and Spearman rank correlation tests. In the qualitative method, interviews were conducted with teachers to determine the factors that contribute to teacher performance. The study's results indicate that there is a relationship or influence of report cards on the performance of SDIT Nurul 'Ilmi Jambi teachers, and there is a powerful positive influence. Other things that influence teacher performance based on the interview results are awareness, concern, and spiritual values such as sincerity and charity for the teacher himself.   Abstrak Rapor guru merupakan sarana komunikasi dan evaluasi antara kepala sekolah dan guru yang dapat meningkatkan kinerja guru serta akan berdampak kepada prestasi belajar siswa. SDIT Nurul ‘Ilmi Jambi telah melaksanakan penerapan rapor guru selama lebih dari 10 tahun yang diberikan pada tiap awal bulan bersamaan dengan penerimaan hak bulanan guru. Penelitian ini bertujuan untuk mengetahui hubungan atau pengaruh rapor terhadap kinerja guru SDIT Nurul ‘Ilmi Jambi. Penelitian ini menggunakan metode campuran (mixed methods), di mana pengumpulan data dilakukan menyebarkan kuesioner, kemudian untuk menganalisis data digunakan alat bantu berupa SPSS dengan uji validitas, uji reliabilitas, dan uji korelasi rank spearman. Sedangkan metode kualitatif, dilakukan wawancara dengan guru untuk mengetahui faktor-faktor yang berkontribusi terhadap kinerja guru. Hasil penelitian menunjukkan bahwa terdapat hubungan atau pengaruh rapor terhadap kinerja guru SDIT Nurul ‘Ilmi Jambi dan adanya pengaruh positif sangat kuat. Hal lain yang memengaruhi kinerja guru dari hasil wawancara adalah kesadaran, kepedulian, dan nilai-nilai spiritualitas seperti keikhlasan dan amal jariyah bagi guru itu sendiri. Kata Kunci: guru sekolah dasar; rapor guru; sekolah dasar